LIVING IN CYBERSPACE: Video Games, Facebook, and the Image of God - Herzfeld, Noreen (Journal of Dharma, 2011)
My home town, Cold Spring Minnesota, is just a few miles from Garrison Keillor's mythical Lake Woebegone. It's the sort of town where neighbour's look in on each other and doors are often left unlocked. As in Lake Woebegone, the children are all above average. A few years ago, one of those children, 15 year old Jason McLaughlin, brought a .22 calibre Colt semi-automatic to school and shot two of his classmates. As with similar school shootings at Columbine, Paducah, Springfield, the media was quick to note that the boy had been an avid video game player. This could, however, go without saying. In a survey of 778 students in grades four through twelve conducted in December 2003, the National Institute on Media and the Family found that 96% of the boys reported playing video games regularly.' A 2007 study of students in grades 3 to 5 showed that boys play video games an average of 14 hours per week, while girls play an average of 4-5 hours. Tween (those ages 8 to 12) and teen boys average 16 hours and 18 hours per week, respectively' Adult players also add to the $10 billion a year industry; the average gamer is 34 years old.